CISSP cert guide - McMillan, Troy (Pearson, 2014)
Learn, prepare, and practice for CISSP exam success with the CISSP Cert Guide from Pearson IT Certification, a leader in IT Certification. Master CISSP exam topicsAssess your knowledge with chapter-ending quizzesReview key concepts with exam preparation tasksPractice with realistic exam questions on the CD" ""CISSP Cert Guide" is a best-of-breed exam study guide. Leading IT certification experts Troy McMillan and Robin Abernathy share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. You'll get a complete test preparation routine organized around proven series elements and techniques.